Effect of Different Environmental Conditions on Durabilities of Polyester- and Vinylester-Based Glass-Fiber-Reinforced Polymer Pultruded Profiles - Yang, Shulan; Chu, Mingkun; Chen, Fangyi; Fu, Miaorui; Lv, Yiwen; Xiao, Ziyi; Feng, Ningning; Song, Yang; Li, Jiannan (Frontiers in Materials, 2022)
This paper presents the results of experimental investigations on the durability of glass-fiber-reinforced polymer (GFRP) pultruded profiles made of unsaturated polyester (UP) and vinylester (VE) resins commonly used in civil engineering. The water absorption, tensile properties, and micro-structures of GFRP profiles exposed to several typical accelerated aging environments (e.g., deionized water, salt water, salt fog, and combined hygrothermal cycles) for 12 months were investigated. Moreover, sustained loading factor was included in the test to reflect the behavior of the GFRP profiles in real structures. A normalization approach based on the controlled specimens was used to assess the effectiveness and relevance of the accelerated exposure. The results indicated that the maximum moisture absorption of both UP and VE GFRP profiles were immersed in deionized water, the masses increased by 1.03% and 0.53%, respectively. The corresponding maximum moisture absorption of both UP and VE GFRP profiles were exposed to combined hygrothermal cycles, the masses increased by 0.09% and 0.06%, respectively. After 360 days of aging, the maximum tensile strength of UP GFRP profiles decreased to 75.97% immersion in deionized water, and the maximum tensile modulus decreased by 47.03% exposed to combined hygrothermal cycles. Whereas, the equivalent respective losses were 15.08% and 22.95% for VE GFRP profiles immersed in deionized water. Furthermore, the sustained loading provided 4.5% degradation of tensile strength and 2.3% degradation of higher elastic modulus than the corresponding unloaded specimens. Finally, by incorporating the cumulative damage caused by the sustained loading and a time-dependent factor into a residual strength model, a revised model was proposed to describe the tensile strength loss of pultruded UP GFRP profiles.